IDENTITAS GARAP MUSIK JOMBANGAN PADA KESENIAN JARANAN DOR DI KABUPATEN KEDIRI - Andre Prasetya Nugraha; Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
This study aims to analyze the identity of Jombangan music garap and its forming factors in the art of Jaranan Dor art group